The Influence of Inquiry Learning Based on Socio-Scientific Issues (SSI) on High School Students' Inquiry Skills and Chemical Literacy - Dewi, Rika Masrina; Prodjosantoso, AK. (Jurnal Penelitian Pendidikan IPA, 2024)
This research examines the effect of SSI-based inquiry learning compared to discovery learning on students' chemical literacy abilities and inquiry skills. It also explores the percentage contribution of SSI-based inquiry learning to these abilities, along with the percentage of students achieving good levels in both areas. The study follows a quasi-experimental design with pretest, treatment, and posttest stages. The population includes all XI-grade students in MAN South Aceh Regency, with a sample drawn from two classes at MAN 4 South Aceh (XI IPA1 and XI IPA2). Data was collected using questions, observation sheets, and questionnaires, and analyzed through MANOVA and N-gain tests. The results indicate a significant difference in chemical literacy and inquiry skills between students using SSI-based inquiry learning and those applying discovery learning. Students engaged in SSI-based inquiry learning performed better in both areas. The study found that SSI-based inquiry learning contributes 92.80% to the improvement of students' chemical literacy and inquiry skills, with 80.90% contributing to chemical literacy and 83.20% to inquiry skills. Additionally, 82% of students in SSI-based inquiry learning show good chemical literacy, while 50% demonstrate good inquiry skills